Hanford and the environment [videorecording (VHS)] - Chin, Sue; Berg, Daniel (The Laboratory?, 1990)
Discusses the effects of the Hanford Site on the environment and how various state and federal agencies monitor those effects. Discusses the keys to Hanford's new mission of environmental safety and health.